Advanced Multifunctional Aqueous Rechargeable Batteries Design: From Materials and Devices to Systems. Issue 5 (24th October 2021) - Li, Lei; Zhang, Qichong; He, Bing; Pan, Rui; Wang, Zhixun; Chen, Mengxiao; Wang, Zhe; Yin, Kuibo; Yao, Yagang; Wei, Lei; Sun, Litao
Abstract: Multifunctional aqueous rechargeable batteries (MARBs) are regarded as safe, cost‐effective, and scalable electrochemical energy storage devices, which offer additional functionalities that conventional batteries cannot achieve, which ideally leads to unprecedented applications. Although MARBs are among the most exciting and rapidly growing topics in scientific research and industrial development nowadays, a systematic summary of the evolution and advances in the field of MARBs is still not available. Therefore, the review presented comprehensively and systematically summarizes the design principles and the recent advances of MARBs by categories of smart ARBs and integrated systems, together with an analysis of their device design and configuration, electrochemical performance, and diverse smart functions. The two most promising strategies to construct novel MARBs may be A) the introduction of functional materials into ARB components, and B) integration of ARBs with other functional devices. The ongoing challenges and future perspectives in this research and development field are outlined to foster the future development of MARBs. Finally, the most important upcoming research directions in this rapidly developing field are highlighted that may be most promising to lead to the commercialization of MARBs and to a further broadening of their range of applications. Abstract : Multifunctional aqueous rechargeable batteries (MARBs) can provide additional functions to realize unprecedented applications where conventional batteries normally fail. This review describes the recent advances of MARBs in terms of materials engineering, device design, system integration, and applications. The challenges and opportunities for further developments in the emerging field of MARBs are deeply discussed.